2000
DOI: 10.2527/2000.7861450x
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of goats: effects on physiological stress responses and live weight loss.

Abstract: The management of food animals prior to slaughter influences both profitability and animal well-being. This experiment was conducted as a split-unit design to determine live weight shrink and stress responses in goats due to differences in stocking density during transportation and holding. A total of 150 Spanish does were transported on two different days (replicate) and held overnight (18 h) without feed in low- (LD) or high-density (HD) groups. On each day, 75 does were transported 2.5 h with floor spaces o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
184
9
33

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(262 citation statements)
references
References 33 publications
36
184
9
33
Order By: Relevance
“…Transportation can be a strong stress for domestic animals [12,13] and it causes weight loss in goats [9] or dark cutting beef (DCB), which is an undesirable, dark, firm, and dry lean surface of beef in cattle [16]. Furthermore, the occurrence of DCB in steers is modulated by implantation of gonadal hormones [16].…”
mentioning
confidence: 99%
“…Transportation can be a strong stress for domestic animals [12,13] and it causes weight loss in goats [9] or dark cutting beef (DCB), which is an undesirable, dark, firm, and dry lean surface of beef in cattle [16]. Furthermore, the occurrence of DCB in steers is modulated by implantation of gonadal hormones [16].…”
mentioning
confidence: 99%
“…In agreement with the current result, Anderson et al (1999) and Zapata et al (2004) also reported a significant increase in plasma cortisol concentration due to transportation stress in guanacos (37.3 nmol L -1 ), finding that values returned to baseline 2 h post-transport (25.4 nmol L -1 ). Kannan et al (2000) found that cortisol values in goats decreased to the baseline level at 1 h after transportation, remained at that level during 18 h and increased again at 18 h probably due to feed deprivation stress. According to Tadich et al (2009) the increased cortisol concentration in lambs after transport is likely to be due to the stress of unloading, handling and bleeding procedure, more than to transport itself, especially considering that from the start of the unloading to the time of bleeding there was a 30 minute interval, as in this case also.…”
Section: Blood Constituentsmentioning
confidence: 99%
“…The blood was stored at 4 °C until centrifugation to obtain the plasma, and plasma was then aliquoted into Eppendorf tubes and frozen at -20 °C until it was thawed for further experimentation. Plasma glucose, lactate, cortisol, NEFAs and CK activity were analyzed according to the methods of Kannan et al (2000Kannan et al ( , 2002.…”
Section: Measurements and Analytical Methodsmentioning
confidence: 99%
“…Elevated plasma levels of cortisol (Sevi et al, 2001), lactate and glucose (Kannan et al, 2000) are associated with stress. Similarly, other authors (Kannan et al, 2007) have suggested that the temperament and behavior of animals can cause variability in plasma concentration of CK.…”
Section: Introductionmentioning
confidence: 99%